Inovasi Pelayanan Dalam Mendukung Startup Inkubasi di Sektor Industri Kecil dan Menengah Oleh Dinas Perindustrian, Perdagangan Energi dan Sumberdaya Mineral Kabupaten Garut - Maharani, Sinta; Wiryandini, Nafisha; Fikri, Hikmal; Aldikri, Zibran; Ariffin, R. Hari Busthomi (Indonesian Journal Publisher, 2025)
This study aims to analyze public service innovation implemented by the Department of Industry and Trade (Disperindag) of Garut Regency in supporting startup incubation programs for Small and Medium Industries (SMEs). The research background highlights the challenges faced by SMEs, including limited market access, low digital literacy, and infrastructure barriers. This study employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. Data analysis uses Rogers’ Diffusion of Innovation theory, which consists of five dimensions: relative advantage, compatibility, complexity, trialability, and observability. The findings reveal that service innovation in the form of startup incubation programs provides relative advantages for SMEs through mentoring, networking facilitation, and digital marketing. However, challenges arise in terms of program compatibility and complexity, particularly among traditional SMEs. In terms of implementation, the program is carried out gradually (trialability) through pilot projects and mentoring, and shows observable impacts (observability) such as increased sales, participation in exhibitions, and marketplace adoption, although the benefits are not yet evenly distributed.